Incidence and Risk Factors for Tuberculosis After Liver Transplantation in an Endemic Area: A Nationwide Population‐Based Matched Cohort Study. Issue 8 (14th April 2015) - Chen, C.‐Y.; Liu, C.‐J.; Feng, J.‐Y.; Loong, C.‐C.; Liu, C.; Hsia, C.‐Y.; Hu, L.‐Y.; Lin, N.‐C.; Hu, Y.‐W.; Yeh, C.‐M.; Chen, T.‐J.; Yang, C.‐C.
<x xml:space="preserve">Abstract</x> Morbidity and mortality from tuberculosis (TB) are high in Taiwan. We conducted a nationwide population‐based matched cohort study using data retrieved from the Taiwan's National Health Insurance Research Database to determine the impact of TB after liver transplantation (LT). During 2000–2011, we identified 3202 liver transplant recipients and selected subjects from the general population matched for age, sex, and comorbidities on the same index date of recognition of LT with a 1:10 ratio. The data were analyzed using Cox proportional hazards models. Compared to the matched cohort, liver transplant patients had a higher risk for TB (adjusted HR 2.25, 95% CI 1.65–3.05, p < 0.001), and those with TB showed higher mortality (HR 2.27, 95% CI 1.30–3.97, p = 0.004). Old age (HR 2.64, 95% CI 1.25–5.54, p = 0.011) and mammalian target of rapamycin inhibitors (mTORis) (HR 3.09, 95% CI 1.68–5.69, p < 0.001) were significant risk factors for TB in LT; mTORis were also associated with mortality after adjusting for confounders (HR 2.13, 95% CI 1.73–2.62, p < 0.001). Therefore, regular surveillance of TB and treatment of latent TB infection in high‐risk patients after LT are important, especially in TB‐endemic areas.